Nadenke oor die kerkbegrip: Enkele perspektiewe op grond van die Deuteronomistiese geskiedenis - Breytenbach, Andries (Hervormde teologiese studies, 1995)
Reflecting on the concept church: Some perspectives from Deutero-nomistic history. This article seeks to explain why and how the Old Testament and Deuteronomistic history in particular are essential in our theological reflection on the concept of church. The main trends in the theology of the Deuteronomistic history are discussed, namely that YHWH is a unique, sovereign and almighty God who elected Israel and made a covenant with them. His steadfast love and preparedness to forgive, as well as his judgement on those who disobey him, serve as an appeal to Israel to honor and obey him in absolute loyalty. The article concludes with the notion that the very existence of the religious community is totally de pendatil on the grace and love of God, and that its members are therefore committed to him and to one another with the prophetic word as their hope for the future.